MODIFIKASI MESIN PENGERING DENGAN MEMANFAATKAN UDARA PANAS DARI ELEMEN PEMANAS LISTRIK - Arhamsyah, Muhammad; Syam, Husain; Jamaluddin, Jamaluddin (Universitas Negeri Makassar, 2018)
This study aims to design dryers using air from listric heating elements that can be used in the dry season and the rainy season. This tool can also reduce the use of time and power farmer in drying agricultural produce. This research is a type of engineering research, in this study was designed of a drying machine that utilizes air from listric heating elements. After the drying machine is complete, experiments are carried out to dry upon wet grain and then calculated the decrease in water content for each rack for 6 hours drying. The drying rate upon wet grain uses a dryer by utilizing air from the listric heating element for each rack is a different, the rate in drying rackÂ 6 (1.43%), rack 5 (1.55%), rack 4 (1.75%), rack 3 (1.73%), rack 2 (2.01%), and rack 1 (2.32%)/hour, the matter shows that the distance of the rack with the heat source affects the drying rate. Air dryers of electric heating elements can reduce the use of farmers' time and power in drying one's crops the uponÂ wet grain, since to dry the newly harvested wet grain takes only 5-6 hours in both the dry season and the rainy season